Animal Experiments and the Right to Ask Questions about Them. Issue 3 (July 2017) - Balls, Michael
The 2016 Home Office Statistics reveal little about progress in implementing the Three Rs, and the right to question how laboratory animals are used in Great Britain has been challenged